Social factors influencing the formation of gender identity disorder and its impact on Islamic law / Nurhidayah Muhamad Sharifuddin and Mohd Anuar Ramli - Sharifuddin, Nurhidayah Muhamad; Ramli, Mohd Anuar (Center for Islamic Philantrophy & Social Finance (CIPSF), 2023)
The advancements in science and technology today have introduced various methods to fulfil human satisfaction, even if they contradict Islamic values and local cultural norms. Discussions about gender identity and gender, which are becoming increasingly widespread, reveal many individuals advocating for and recognizing their status in society, especially transgender individuals. Therefore, this study will discuss the factors contributing to the development of Gender Identity Disorder within them and its implications for Islamic law. To achieve this objective, this study adopts a qualitative approach, applying content analysis methods to past studies, and utilizes thematic analysis methods. The study results indicate four factors that contribute to the development of Gender Identity Disorder in an individual: life experiences, parental desires, peer influences, and the influence of new media. Consequently, various stigmas and discrimination are imposed upon them. Islam clearly prohibits acts that contradict and alter Allah's creation. Thus, positive support and assistance from society are necessary to prevent these individuals from feeling marginalized. They need the best recovery treatment to restore them to their fitrah.